Analisis dan Perancangan Aplikasi Penganggaran Barang berbasis Web pada Unit Sarana Prasarana Perguruan Tinggi - Maharani, Siti Zahra; Adriansyah, Ahmad Rio (Jurnal Informatika Terpadu, 2022)
This study discusses the budget approval process at the Nurul Fikri Integrated Technology High School Facilities and Infrastructure Unit, which is inflexible because it requires a physical supervisor's signature, management of the procurement of goods that have not been carried out centrally and is expected to reduce delays in the fulfillment of goods and repetitive work. Therefore, an STT-NF Goods Budgeting application is needed to facilitate submissions and streamline time in meeting the needs of goods and data backup. The method used in designing the STT-NF Goods Budgeting application uses a literature review, interviews with the head of the Integrated High School Facilities and Infrastructure Section, Nurul Fikri, and the Incremental Development System method in stages. The study results showed the suitability of the features as expected; 96% of users stated that the features in the information system were by the process of submitting existing goods.